La Sacralisation littéraire et picturale de la montagne au XIXe siècle : (re)naissances et épiphanies - Françoise Dupeyron-Lafay (Anglophonia)
Mountains, that had been objects of indifference, fear, or even terror and loathing until the mid-18th century, became literary and pictorial subjects in their own right from the Romantic period onwards, especially in the wake of Rousseau’s La Nouvelle Héloïse (1761)—that radically changed the approach to nature—, and the first ascents of Mont Blanc in the 1780s that marked the beginning of Alpine tourism, and turned Chamonix (and later the Swiss Alps) into indispensable features of the "Grand Tour". We shall see the various—and sometimes complementary and converging—approaches to mountains from the late 18th century on: those emphasizing their pristine, Edenic nature; those extolling their power, sublimity and elemental violence, Turner’s paintings being emblematic in this respect : and those bringing out their divine essence, their sacred and holy quality. The corpus will mainly pertain to the latter category and through the study of Novalis, De Quincey, Ruskin, and Caspar David Friedrich’s paintings, we shall discover stories of birth and rebirth, regeneration and redemption. In the works of these authors, mountains—whether real or merely imaginary, whether the results of experience or pure fantasy—are nevertheless the locus of intense epiphanies leading to the advent of the self as true individual and artist